Meaning and Usage of Jibun in Oral Japanese - Mercy Riyanto; Hari Setiawan; Robihim Robihim (Universitas Negeri Semarang, 2023)
This study analyzes the meaning of using the word Jibun in spoken language taken from the story of a smartphone game entitled